3D scaffold alters cellular response to graphene in a polymer composite for orthopedic applications. Issue 4 (20th October 2015) - Kumar, Sachin; Azam, Dilkash; Raj, Shammy; Kolanthai, Elayaraja; Vasu, K.S.; Sood, A.K.; Chatterjee, Kaushik
Abstract: Graphene‐based polymer nanocomposites are being studied for biomedical applications. Polymer nanocomposites can be processed differently to generate planar two‐dimensional (2D) substrates and porous three‐dimensional (3D) scaffolds. The objective of this work was to investigate potential differences in biological response to graphene in polymer composites in the form of 2D substrates and 3D scaffolds. Polycaprolactone (PCL) nanocomposites were prepared by incorporating 1% of graphene oxide (GO) and reduced graphene oxide (RGO). GO increased modulus and strength of PCL by 44 and 22% respectively, whereas RGO increased modulus and strength by 22 and 16%, respectively. RGO increased the water contact angle of PCL from 81° to 87° whereas GO decreased it to 77°. In 2D, osteoblast proliferated 15% more on GO composites than on PCL whereas RGO composite showed 17% decrease in cell proliferation, which may be attributed to differences in water wettability. In 3D, initial cell proliferation was markedly retarded in both GO (36% lower) and RGO (55% lower) composites owing to increased roughness due to the presence of the protruding nanoparticles. Cells organized into aggregates in 3D in contrast to spread and randomly distributed cells on 2D discs due to the macro‐porous architecture of the scaffolds. Increased cell‐cell contact and altered cellular morphology led to significantly higher mineralization in 3D. This study demonstrates that the cellular response to nanoparticles in composites can change markedly by varying the processing route and has implications for designing orthopedic implants such as resorbable fracture fixation devices and tissue scaffolds using such nanocomposites. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 732–749, 2016.